Striga Resistance in Cereal Crops: Recent Progress and Future Prospects. A Review (Global Journal of Science Frontier Research, 2017)
Production of cereal crops such as sorghum, maize, rice and millet is threatened by Striga hermonthica (Del.) Benth and Striga asiatica (L.) Kuntze in sub-Saharan Africa and India. Varying levels of resistance have been identified and exploited in the breeding programmes of several crops. Considerable efforts have been invested in breeding for Striga resistance in cereals and significant progress has been made in the development of improved selection methods. However, the level of protection achieved to date is incomplete especially for orphan crops such as pearl millet. Resistance is mainly determined by the coexistence of several mechanisms controlled by multigenic and quantitative systems. Efficient control of the parasite requires a better understanding of the interaction and their associated resistance mechanisms at the histological, genetic and molecular levels. Application of postgenomic technologies and the use of model plants should improve the understanding of the plant–parasitic plant interaction and drive not only breeding programmes through either marker-assisted selection (MAS) or transgenesis but also the development of alternative methods to control the parasite. However, it is only a beginning that requires to be further exploited. This review presents an overview on recent advances in research on Striga in cereals and potential prospects using genomic tools as mentioned above with a final aim of crop improvement.
Keywords: striga spp; resistance; cereals; recent progress; potential prospects